Identification of proteins in promastigote and amastigote-like Leishmania using an immunoproteomic approach. - Vinicio T S Coelho (Public Library of Science (PLoS), 2012)
Background The present study aims to identify antigens in protein extracts of promastigote and amastigote-like Leishmania (Leishmania) chagasi syn. L. (L.) infantum recognized by antibodies present in the sera of dogs with asymptomatic and symptomatic visceral leishmaniasis (VL). Methodology/principal findings Proteins recognized by sera samples were separated by two-dimensional electrophoresis (2DE) and identified by mass spectrometry. A total of 550 spots were observed in the 2DE gels, and approximately 104 proteins were identified. Several stage-specific proteins could be identified by either or both classes of sera, including, as expected, previously known proteins identified as diagnosis, virulence factors, drug targets, or vaccine candidates. Three, seven, and five hypothetical proteins could be identified in promastigote antigenic extracts; while two, eleven, and three hypothetical proteins could be identified in amastigote-like antigenic extracts by asymptomatic and symptomatic sera, as well as a combination of both, respectively. Conclusions/significance The present study represents a significant contribution not only in identifying stage-specific L. infantum molecules, but also in revealing the expression of a large number of hypothetical proteins. Moreover, when combined, the identified proteins constitute a significant source of information for the improvement of diagnostic tools and/or vaccine development to VL.